2017
DOI: 10.1556/004.2017.021
|View full text |Cite
|
Sign up to set email alerts
|

Control of Hymenolepis nana infection as a measure to improve mouse colony welfare

Abstract: After cannibalism had appeared in the reproductive units of a white mouse colony, treatment against confirmed Hymenolepis nana, a tapeworm with zoonotic potential, was performed on 67 mice in the reproductive and nursery units. Faecal droppings were evaluated by flotation and sedimentation methods. The sedimentation method revealed a higher number of positive results before, during and after the treatment, but the flotation method yielded some additional positive cases. In the reproductive unit, H. nana eggs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…A close phylogenetic match to H. microstoma was also determined in the tapeworm derived from captive dormouse (Muscardinus avellanarius) in the United Kingdom (Peniche et al, 2017). The dwarf tapeworm H. nana is the only cestode recognized as not requiring an intermediate host to develop into maturity under natural conditions (Dovč et al, 2017). The potential capability of the direct life cycle for H. microstoma (as another common feature with H. nana) has been discussed in the literature in the past (Skrjabin & Kalantarian, 1942;Macnish et al, 2003), and later evidenced in immunocompromised mice by Andreassen et al (2004) who showed that oncospheres penetrated the intestinal tissues and developed into cysticercoids and subsequently into the adult stage in the bile duct and duodenum when infected with parasite eggs.…”
Section: Discussionmentioning
confidence: 81%
“…A close phylogenetic match to H. microstoma was also determined in the tapeworm derived from captive dormouse (Muscardinus avellanarius) in the United Kingdom (Peniche et al, 2017). The dwarf tapeworm H. nana is the only cestode recognized as not requiring an intermediate host to develop into maturity under natural conditions (Dovč et al, 2017). The potential capability of the direct life cycle for H. microstoma (as another common feature with H. nana) has been discussed in the literature in the past (Skrjabin & Kalantarian, 1942;Macnish et al, 2003), and later evidenced in immunocompromised mice by Andreassen et al (2004) who showed that oncospheres penetrated the intestinal tissues and developed into cysticercoids and subsequently into the adult stage in the bile duct and duodenum when infected with parasite eggs.…”
Section: Discussionmentioning
confidence: 81%
“…After 5 min, the coverslip was removed and placed on a pre-numbered slide for examination under a light microscope at 40× magnification (Dryden et al, 2005). The diagnosis of H. nana infection was confirmed by the finding of the polar filament of dark brown-colored eggs (Dovč et al, 2017).…”
Section: Flotation Techniquementioning
confidence: 94%